Multicenter retrospective study to evaluate the efficacy and safety of the double‐flap technique as antireflux esophagogastrostomy after proximal gastrectomy (rD‐FLAP Study). Issue 1 (11th October 2018) - Kuroda, Shinji; Choda, Yasuhiro; Otsuka, Shinya; Ueyama, Satoshi; Tanaka, Norimitsu; Muraoka, Atsushi; Hato, Shinji; Kimura, Toshikazu; Tanakaya, Kohji; Kikuchi, Satoru; Tanabe, Shunsuke; Noma, Kazuhiro; et al.
Abstract: Aim: As a result of the difficulty in effective prevention of gastroesophageal reflux, no standard reconstruction procedure after proximal gastrectomy (PG) has yet been established. The double‐flap technique (DFT), or Kamikawa procedure, is an antireflux reconstruction procedure in esophagogastrostomy. The efficacy of DFT has recently been reported in several studies. However, these were all single‐center studies with a limited number of cases. Methods: We conducted a multicenter retrospective study in which patients who underwent DFT, irrespective of disease type and reconstruction approach, at each participating institution between 1996 and 2015 were registered. Primary endpoint was incidence of reflux esophagitis at 1‐year after surgery, and secondary endpoint was incidence of anastomosis‐related complications. Results: Of 546 patients who were eligible for this study, 464 patients who had endoscopic examination at 1‐year follow up were evaluated for reflux esophagitis. Incidence of reflux esophagitis of all grades was 10.6% and that of grade B or higher was 6.0%. Male gender and anastomosis located in the mediastinum/intra‐thorax were independent risk factors for grade B or higher reflux esophagitis (odds ratio [OR]: 4.21, 95% confidence interval [CI]: 1.44‐10.9, P  =   0.0109). Total incidence of anastomosis‐related complications was 7.2%, including leakage in 1.5%, strictures in 5.5% and bleeding in 0.6% of cases. Laparoscopic reconstruction was the only independent risk factor for anastomosis‐related complications (OR: 3.93, 95% CI: 1.93‐7.80, P  =   0.0003). Conclusion: Double‐flap technique might be a feasible option after PG for effective prevention of reflux, although anastomotic stricture is a complication that must be well‐prepared for. Abstract : A multicenter retrospective study in which 546 patients who underwent the double‐flap technique (DFT), irrespective of disease type and reconstruction approach, at each participating institution between 1996 and 2015 were registered, showed that the incidence of reflux esophagitis of all grades was 10.6% and that of grade B or higher was 6.0%, and the total incidence of anastomosis‐related complications was 7.2%, including leakage in 1.5%, strictures in 5.5% and bleeding in 0.6% of cases. DFT might be a feasible option after proximal gastrectomy for effective prevention of reflux, although anastomotic stricture is a complication that must be well‐prepared for.